Effects of competitive psychological climate, work-family conflict and role conflict on customer orientation: The case of call center employees in India. Issue 1 (14th May 2014) - Sahadev, Sunil; Seshanna, Sudarshan; Purani, Keyoor
Abstract : Purpose: – The purpose of this paper is to consider the impact of a competitive psychological climate on the levels of role conflict and work-family conflict in call center employees and their further impact on customer orientation. Design/methodology/approach: – The conceptual model is developed through a review of literature and is then validated in the context of call center employees in India. A total of 281 responses were considered. The model is validated using a multi-group analysis in order to consider a possible influence of gender. Findings: – The model is found to have a very good fit and four of the five hypothesized relationships are found to be significant. The study thus establishes the impact of a competitive psychological climate on the role conflict and work-life conflict in the case of service employees. Research limitations/implications: – The study uses a self-reported measure of customer orientation as well as the sampling methodology is not random. These two aspects could limit the generalizability of the results. Practical implications: – The paper gives empirical support against adoption of competition-based practices in service organizations. This is an important implication for practitioners. Originality/value: – The study looks at the impact of competitive psychological climate in call centers, a construct hitherto not much analyzed. The analysis of the relationship between competitive psychological climate, role conflict and work-family conflict have also not been looked into in the previous literature.